Norm und Zeremoniell Das Etiquette-Normale für den Wiener Hof von circa 1812 - Schneider, Karin (2019)
Between 1810 and 1813 the Master of Ceremonies Count Gundacker Heinrich Wurmbrand drafted an "Etiquette-Normale für den österreichischen Kaiserhof", which is a unique source for the reconstruction of everyday ceremonies at the Viennese court after the Napoleonic era. The text define the role of the Emperor, the ranks of the members of his entourage and the status of the court servants in a complex, symbolic system of relations. Court and court society are presented as a well-ordered mechanism to celebrate the dignity and rank of the Austrian Empire invented in 1804 and to legitimize it through symbolic communication.